(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The refugee crisis, particularly the Syrian refugee crisis, has become a pressing global challenge, prompting discussions on moral, political, and humanitarian responsibilities. Literature has emerged as a powerful medium to explore and understand the experiences of refugees. This study aims to explore the role of refugee literature in shaping our understanding of the Syrian refugee crisis and its broader implications. It delves into the historical context of the crisis, highlighting the deep-rooted issues that led to the conflict. Refugee literature serves as a means of bearing witness to the crisis, providing firsthand accounts and testimonies of refugees’ experiences. It challenges stereotypes and misconceptions surrounding refugees, offering alternative perspectives on their lives and highlighting their cultural contributions. The literature also portrays the dynamics between host communities and refugees, shedding light on the tensions and conflicts that arise. Furthermore, it addresses issues affecting refugees and advocates for their rights and dignity. Refugee literature has the potential to shape public opinion and influence policy, fostering empathy and inspiring action. Engaging with these literary works can lead to a more inclusive and compassionate approach to the refugee crisis, promoting a global society that values the well-being of all individuals, regardless of their place of origin.